The Effects of Responsibility and Empathy on Customer Satisfaction in Teaching Factory Learning - Sudrajat, Surya Catur; Buditjahjanto, I Gusti Putu Asto; Warju, Warju (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Vocational education encourages students to achieve competency in order to make students more prepared when joining the world. In order to achieve this goal, vocational education applies the model of a teaching factory. In factory learning, students are taught to provide direct services and products suitable for sale to general consumers or the public. Fundamental values ​​such as responsibility, empathy, and cooperation in service to society are the keys to this learning. The research aims to determine the simultaneous influence of responsibility and empathy on customer satisfaction in teaching factory learning at UPJ Vehicle Engineering Vocational High School 1 Bendo. The research used a sample of 67 class XII students at Vocational High School 1 Bendo using a Likert scale questionnaire with instrument validity test results using V-Aiken and reliability testing using Cronbach alpha. The research uses multiple linear regression analysis for the independent variables (responsibility and empathy) and the dependent (customer satisfaction) variables. The results of the Anova significance research were 0.000, and the calculated F value was 358.402. Then, the R2 value was 0.964. This shows that responsibility and empathy significantly influence customer satisfaction, with a percentage of 96.4%. Hopefully, this research can become the basis for further policy-making.